Stories from Mexico - Dolch, Edward William 1889-1961 (Folklore of the world, 1960)
Tales from Mexican folklore including The Palace of Canela, In Through the Window, The Coyote and the Sheep, The Cu Bird, and Senaor Coyote and Juan's Maguey.